2013
DOI: 10.1186/1757-2215-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Pronuclear morphology evaluation in in vitro fertilization (IVF) / intracytoplasmic sperm injection (ICSI) cycles: a retrospective clinical review

Abstract: BackgroundThe assessment of the embryo quality is crucial to maintain an high pregnancy rate and to reduce the risk of multiple pregnancy. The evaluation of the pronuclear and nucleolar characteristics of human zygote have been proposed as an indicator of embryo development and chromosomal complement. The aim of the current study was to assess the role of pronuclear morphology evaluation in vitro fertilization (IVF) / intracytoplasmic sperm injection (ICSI) cycles.MethodsRetrospective clinical analysis on 755 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…KRAS-variant is found to be a genetic marker for increased risk of developing ovarian cancer [7]. Genes related with cell cycle, lipid metabolism and cytoskeletal structure are screened as the treatment targets for ovarian cancer [8]. …”
Section: Introductionmentioning
confidence: 99%
“…KRAS-variant is found to be a genetic marker for increased risk of developing ovarian cancer [7]. Genes related with cell cycle, lipid metabolism and cytoskeletal structure are screened as the treatment targets for ovarian cancer [8]. …”
Section: Introductionmentioning
confidence: 99%
“…From 2000 to 2003, the majority of the studies published showed that the zygote morphology significantly correlated with the pregnancy rates [10-14,19,21,23]. In the subsequent years until today, this trend has significantly changed, due to the publication of studies in contrast with earlier data [25,26,28,30,32,34,38,40],[46,49]. …”
Section: Resultsmentioning
confidence: 99%
“…One study (25.0%) found a significant correlation [36], whereas 3 (75.0%) did not find any relationship [30,46,49]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover most investigations have evaluated ED but not fertilization, determined by PN formation, to assure that the zygotes are diploid. This condition is essential for the normal development of the embryos [23]. When oocytes are artificially activated, a high probability that the resultant blastocysts will be parthenogenic exists [17, 24, 25].…”
Section: Introductionmentioning
confidence: 99%